Effects of health decentralization, financing and governance in Mexico - Armando Arredondo; Emanuel Orozco (Universidade de São Paulo, 2006)
OBJECTIVE: To identify the effects of decentralization on health financing and governance policies in Mexico from the perspective of users and providers. METHODS: A cross-sectional study was carried out in four states that were selected according to geopolitical and administrative criteria. Four indicators were assessed: changes and effects on governance, financing sources and funds, the final destination of resources, and fund allocation mechanisms. Data collection was performed using in-depth interviews with health system key personnel and community leaders, consensus techniques and document analyses. The interviews were transcribed and analyzed by thematic segmentation. RESULTS: The results show different effectiveness levels for the four states regarding changes in financing policies and community participation. Effects on health financing after decentralization were identified in each state, including: greater participation of municipal and state governments in health expenditure, increased financial participation of households, greater community participation in low-income states, duality and confusion in the new mechanisms for coordination among the three government levels, absence of an accountability system, lack of human resources and technical skills to implement, monitor and evaluate changes in financing. CONCLUSIONS: In general, positive and negative effects of decentralization on health financing and governance were identified. The effects mentioned by health service providers and users were related to a diversification of financing sources, a greater margin for decisions around the use and final destination of financial resources and normative development for the use of resources. At the community level, direct financial contributions were mentioned, as well as in-kind contributions, particularly in the form of community work.